Establishment of National Public Audit Oversight Boards: Descriptive Evidence and Implications for Audit Quality - CARSON, ELIZABETH; LAMOREAUX, PHILLIP; SIMNETT, ROGER; THÜRHEIMER, ULRIKE; VANSTRAELEN, ANN (Journal of Accounting Research, 2026)
ABSTRACT We investigate the establishment of public audit oversight bodies (POBs) worldwide. We present descriptive evidence on POBs’ characteristics and factors influencing the timing of their establishment, finding that countries with stronger institutions, civil law traditions, and higher media attention to audit quality adopt POBs faster. While countries may choose similar POB design features, these choices do not align with the factors driving adoption speed. We also explore whether the finding of a positive impact on audit quality of the U.S. PCAOB generalizes to other countries. A difference‐in‐differences analysis over 20 years provides some evidence that POB establishment and their characteristics improve audit quality. However, the results appear sensitive to audit quality measures and research design. Our study offers the first broad‐based investigation of POB adoption and provides important nuance on the relation between POBs and audit quality.